2016
DOI: 10.1155/2016/7061587
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antimicrobial Activity of Chlorhexidine, Coconut Oil, Probiotics, and Ketoconazole onCandida albicansIsolated in Children with Early Childhood Caries: An In Vitro Study

Abstract: Background. Early childhood caries (ECC) is associated with early colonisation and high levels of cariogenic microorganisms. With C. albicans being one of those, there is a need to determine the effectiveness of various chemotherapeutic agents against it. The study is aimed at isolating Candida species in children with ECC and at studying the antifungal effect of coconut oil, probiotics, Lactobacillus, and 0.2% chlorhexidine on C. albicans in comparison with ketoconazole. Materials and Methods. Samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
4
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 19 publications
2
33
4
7
Order By: Relevance
“…A widely prescribed mouth rinse, chlorhexidine has shown good clinical results as an alternative to conventional antifungal agents. [6,7] Chlorhexidine inhibits adhesion of Candida to oral and mucosal surfaces. It causes coagulation of nucleoproteins and also porosities in the cell wall, resulting in extrusion of cytoplasmic components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A widely prescribed mouth rinse, chlorhexidine has shown good clinical results as an alternative to conventional antifungal agents. [6,7] Chlorhexidine inhibits adhesion of Candida to oral and mucosal surfaces. It causes coagulation of nucleoproteins and also porosities in the cell wall, resulting in extrusion of cytoplasmic components.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Another in vitro study showed chlorhexidine to have significant antifungal activity as compared to ketoconazole on Candida albicans isolated from children with early childhood caries. [7] The antifungal action of tulasi is due to its effect on the ergosterol biosynthesis pathway. Ergosterol is a membrane sterol unique to fungi.…”
Section: Discussionmentioning
confidence: 99%
“…The enriched VCO also increased the level of IL-2 while the level of IgG changed from equivocal to negative. Latest, in comparison with ketoconazole, antifungal activity of C. albicans isolated from children with early childhood caries was tested using coconut oil [64] and it was validated that coconut oil had comparable antifungal activity with ketoconazole. The antifungal activity of coconut oil against C. albicans was also found to be higher than probiotic, a live microorganism that grants a health benefit on the host when administered in adequate amounts.…”
Section: E Antifungal Action Of Coconut Oilmentioning
confidence: 99%
“…En particular en personas de edad avanzada y pacientes inmunodeprimidos. Las bacterias probióti-cas se han utilizado para modificar el ecosistema microfloral y han demostrado cierto éxito como agente terapéutico para las enfermedades orales (28) . La ingesta diaria de queso suplementado con L. rhamnosus GG, L. rhamnosus LC705 y Propionibacterium freudenreichii ssp shermanii JS ha obtenido como resultado una reducción de la prevalencia de C. albicans y también un aumento de la salivación.…”
Section: Infección Por Candida Albicans (Candidiasis)unclassified
“…Otro factor importante en relación a esta infección es que el hecho de que el sitio de colonización más alto para Candida albicans es proporcionado por la lesión cariosa, ya que la producción de ácidos favorece un nicho ecológico para este microorganismo. Además, se ha visto en estudios In Vitro que la presencia de Candida albicans mejora la adherencia de S. mutans a la biopelícula oral y en la sustancia dental cariada (28) . Por lo que sería lógico pensar que un mayor control de los patógenos de la caries dental con probióticos tendría como consecuencia adicional una disminución de la incidencia de Candida albicans.…”
Section: Infección Por Candida Albicans (Candidiasis)unclassified